Aortic Annulus Stabilization Technique for Rapid Deployment Aortic Valve Replacement. Issue 5 (September 2015) - Ferrari, Enrico; Siniscalchi, Giuseppe; Tozzi, Piergiorgio; von Segesser, Ludwig
Abstract : Abstract: Rapid deployment aortic valve replacement (RDAVR) with the use of rapid deployment valve systems represents a smart alternative to the use of standard aortic bioprosthesis for aortic valve replacement. Nevertheless, its use is still debatable in patients with pure aortic valve regurgitation or true bicuspid aortic valve because of the risk of postoperative paravalvular leak. To address this issue, an optimal annulus-valve size match seems to be the ideal surgical strategy. This article describes a new technique developed to stabilize the aortic annulus and prevent paravalvular leak after RDAVR. To confirm the feasibility, this technique was performed in six patients with severe symptomatic aortic stenosis who were scheduled to undergo aortic valve replacement at our center. All patients survived surgery and were discharged from the hospital. There were no new intracardiac conduction system disturbances observed, and a permanent pacemaker implantation was not required in any of the patients. The intraoperative and postoperative echocardiogram confirmed successful positioning of the valve, and no paravalvular leak was observed. In this preliminary experience, RDAVR through a full sternotomy or an upper hemisternotomy approach with the use of aortic annulus stabilization technique was safe, and no leak was observed. Future studies on large series of patients are necessary to confirm the safety and effectiveness of this technique in preventing paravalvular leak in patients with true bicuspid aortic valves or pure aortic regurgitation.